Pozitivni vplivi pripovedovanja na otroke in mladostnike - Jamar, Nina (Glasba v šoli in vrtcu, 2024)
This paper explores the benefits of incorporated music-themed storytelling in libraries within music schools. Therefore, we reviewed the literature on the positive effects of storytelling on children and adolescents, using the Grid Engine to search for relevant studies with keywords such as storytelling, children and brain. Several references highlighting the advantages of storytelling for children and teenagers were selected. While the scope of our literature review remains limited, as this is an emerging area of inquiry, the findings underscore the substantial educational value of storytelling. Specifically, storytelling has been shown to positively influence vocabulary acquisition, writing skills, content exploration, self-esteem, imagination, and cultural knowledge. These findings provide a strong rationale for integrating storytelling into library programmes in music school settings.
Keywords: adolescents; children; fairy tales; glasbene šole; Javno nastopanje; mladostniki; music schools; otroci; pravljice; pripovedovanje; storytelling